28-day all-cause mortality and associated factors in cancer patients with bacteremia at a peruvian referral center - Yosué Vera; Nicolás Ismael Zamudio; Bruno Eduardo Rojas; Cesar Cárcamo; Pedro Legua; Brian Delfin; Dany Rivera; Kathiuska Tutaya; Karol Villavicencio; Angie Palomino; Sissy Monsalve; Paola Montenegro; et al. (PLoS ONE, 2026)
Introduction The global prevalence of cancer has increased in recent decades. Cancer patients are especially vulnerable to invasive infections like bacteremia. In Peru, the rising incidence of bloodstream infections caused by resistant pathogens has become a major public health issue. There is limited information about this complication in the Peruvian cancer population. No previous local studies have assessed mortality or explored the impact of antimicrobial resistance on patient outcomes in this group. Methods This study aimed to evaluate 28-day all-cause mortality and its associated factors among cancer patients with bacteremia at a referral cancer center in Lima. We retrospectively analyzed data from first episodes of bacteremia in hospitalized adult patients between July 2020 and June 2024. Results A total of 293 patients were included in the study. The mean age was 65.4 ± 15.3 years, and 53.9% were female. Most patients had solid tumors (84.3%) and active disease (91.8%), with digestive cancers being the most common (34.1%). The 28-day all-cause mortality rate was 32.1%. Empirical antimicrobial therapy was appropriate in 80.7% of cases. Gram-negative bacteria (GNB) predominated (82.8%), with Escherichia coli being the most frequently isolated pathogen (45.7%). Among Enterobacteriaceae, 43.6% were extended-spectrum beta-lactamase (ESBL) producers, and 3.3% of GNB were carbapenem-resistant. Multivariable Poisson regression identified the Charlson Comorbidity Index (RR 1.1; 95% CI 1.1–1.2), sepsis (RR 2.3; 95% CI 1.3–3.8), septic shock (RR 3.0; 95% CI 1.9–4.6), respiratory failure (RR 1.6; 95% CI 1.2–2.2), Coagulase-negative Staphylococci (CoNS) bacteremia (RR 1.8; 95% CI 1.2–2.6) and primary source (RR 2.8; 95% CI 1.5–5.1) as independent factors associated with increased 28-day mortality. Conclusion At this cancer referral center, one-third of patients with bacteremia died within 28 days. Mortality was primarily caused by the severity of infection, comorbidities and specific bacteremia characteristics, rather than antimicrobial resistance.